Spreading and coding for anti-interference in UWB system - XU Chen; ZHANG Shi-bing (Tongxin xuebao)
Spreading every transmitted bit over each sub-band and interleaving the spread signals over all of the sub-bands would provide the robustness to narrow-band interference in the ultra-wide band （UWB） system based on orthogonal frequency-division multiplexing （OFDM）. Simulation results show that the system has evident robustness against narrow-band interference and would improve the performance about 5dB in SIR or 1-2 order in BER.